Theoretical and experimental study on a dual-stage variable stiffness friction damper for satellite flywheel. (15th February 2023) - Liu, Haiping; Mao, Longgan; Wang, Tian; Hou, Yongtao
Abstract: Micro-vibration reduction devices are widely utilized to mitigate disturbances from on-board flywheel in order to enhance the performance for high precision payloads in satellite. However, the conventional micro-vibration suppression devices cannot endure the high-level loadings and effectively control the dynamic responses of the flywheel in launching stage. In this paper, firstly, a new type of dual-stage variable stiffness friction damper (DS-VSFD) is proposed and investigated under the on-orbit and launch loads. In order to demonstrate the effectiveness of the developed damper, the mechanism and hysteresis characteristics of the device are introduced in detail and the variable sliding force and displacement of the DS-VSFD are theoretically analyzed. Based on the relationship between output force and displacement of the device, a double-tail-shaped hysteresis curve is illustrated and corresponding stiffness and energy dissipation capacity at different stages are provided. Secondly, a single-degree-of-freedom dynamic model of the flywheel system with the DS-VSFD is constructed. The Harmonic Balance Method (HBM) is adopted to derive the force and displacement transmissibility curves in the frequency domain based on the dynamic model under different excitation conditions. In on-orbit stage, it can be observed that the resonance frequency is shifted to higher frequency and the amplitude is lower than that of the linear case in higher frequencies. In launching stage, the peak of displacement transmissibility of the flywheel system has been decreased in the resonance region comparing with the conventional linear isolator. Besides, the resonant frequency of the system has shifted to higher frequency region. Effects of the external excitation amplitude on the force transmissibility are also examined. Finally, comparison between the theoretical and experimental results has been carried out through static and dynamic tests. According to the static mechanical experimental results, it can be demonstrated that the DS-VSFD with wedge-block configuration exhibits stable and reliable hysteresis characteristics. The actual experimental results agree with the calculation results of the system dynamics model with the DS-VSFD in terms of force and displacement transmissibility. The results discussed in this research indicate that the DS-VSFD guarantees both the structural safety of the flywheel system under the launch loads and the micro-vibration reduction of the flywheel under the on-orbit condition.